2022
DOI: 10.3389/fgene.2022.870191
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expressions of NF1 and NF1-Related microRNAs as Biomarkers in the Diagnosis of Undifferentiated Pleomorphic Sarcoma

Abstract: Objective: Undifferentiated pleomorphic sarcoma (UPS) is a highly malignant, aggressive, and pleomorphic subtype of soft tissue sarcoma in adults. However, UPS is difficult to be diagnosed due to the lack of specific morphological and immunophenotypic features. Here, we aimed to identify new biomarkers for the diagnosis of UPS.Methods: The mRNA and protein expression of neurofibromin 1 (NF1) in 68 pairs of UPS and adjacent normal tissues were detected by qRT-PCR and immunohistochemistry, and the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A comprehensive genomic analysis has reported that the NF1 gene is one of the most frequently altered genes in soft tissue sarcomas (STS) ( 27 ). Studies have demonstrated that individuals with NF1 mutations are predisposed to developing STS ( 28 ). In vitro experiments, NF1 promotes the initiation and progression of UPS by inhibiting the PI3K-Akt-mTOR-S6 pathway ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive genomic analysis has reported that the NF1 gene is one of the most frequently altered genes in soft tissue sarcomas (STS) ( 27 ). Studies have demonstrated that individuals with NF1 mutations are predisposed to developing STS ( 28 ). In vitro experiments, NF1 promotes the initiation and progression of UPS by inhibiting the PI3K-Akt-mTOR-S6 pathway ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that individuals with NF1 mutations are predisposed to developing STS ( 28 ). In vitro experiments, NF1 promotes the initiation and progression of UPS by inhibiting the PI3K-Akt-mTOR-S6 pathway ( 28 ). PI3K pathway is frequently upregulated in epithelial ovarian cancers and plays an important role in cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Many miRNAs have also been abnormally expressed in STSs, and the knowledge of miRNA expression patterns in STSs could identify specific signatures for the histological subtypes (5,6). Furthermore, the different profiling of miRNA expression in tumor tissue of STSs compared with adjacent tissue may provide a clue for the diagnosis of STSs (7)(8)(9). Many studies recently have demonstrated that the altered expression of miRNAs is associated with the occurrence of numerous diseases, which may have a significant possibility of being used as biomarkers and targets of treatment for human illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive genomic analysis has reported that the NF1 gene is one of the most frequently altered genes in soft tissue sarcomas (STS) (27). Studies have demonstrated that individuals with NF1 mutations are predisposed to developing STS (28). In vitro experiments, NF1 promotes the initiation and progression of UPS by inhibiting the PI3K-Akt-mTOR-S6 pathway (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that individuals with NF1 mutations are predisposed to developing STS (28). In vitro experiments, NF1 promotes the initiation and progression of UPS by inhibiting the PI3K-Akt-mTOR-S6 pathway (28). PI3K pathway is frequently upregulated in epithelial ovarian cancers and plays an important role in cell survival.…”
Section: Discussionmentioning
confidence: 99%